Exchange rate uncertainty and firm investment plans: Evidence from Swiss survey data - Garret Binding; Andreas Dibiasi (ETH Zurich, KOF Swiss Economic Institute, 2016)
A sudden change in monetary policy happened in Switzerland on January 15th, 2015. The Swiss National Bank removed a lower exchange rate bound vis-à-vis the Euro. This unexpected change of regime induced a temporary uncertainty about future prices in foreign markets. We believe that this hampers firm investment in the short term. Using this change in monetary policy as a natural experiment and exploiting the continuous nature of a micro-level business tendency survey, we identify the source of uncertainty and disentangle first and second moment effects. We find that price uncertainty affects investment in equipment and machinery through real option effects and believe that growth option effects positively influences expenditures in research and development. We show that focusing on aggregate gross fixed capital formation masks important insights and suggest the use of disaggregated investment data to deepen our knowledge on the relationship between uncertainty and investment.
Keywords: D81; D84; E22; 330; investment; uncertainty; irreversibility; Switzerland